2008
DOI: 10.1097/01.prs.0000297638.76602.de
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Springs in Craniofacial Surgery: The First 100 Clinical Cases

Abstract: This therapeutic modality in craniofacial surgery has allowed minimization of the extent of surgery without compromising clinical outcomes. Springs have now become part of the authors' treatment protocol for craniosynostosis and midface surgery. The authors have shown the use of these techniques to be safe and, in selected situations, to offer significant advantages over other methods of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(121 citation statements)
references
References 7 publications
11
107
1
2
Order By: Relevance
“…9,12,22 The male to female ratio showed a higher proportion of females with bicoronal and unilateral coronal craniosynostosis, which is similar to results in past studies. 12 Our patients with secondary craniosynostosis had lower mean gestational ages and mean birth weights, which we presume is a natural phenomenon due to overall brain and systemic underdevelopment.…”
Section: Results Of the Tsdo Operative Technique In 285 Children Withsupporting
confidence: 81%
See 1 more Smart Citation
“…9,12,22 The male to female ratio showed a higher proportion of females with bicoronal and unilateral coronal craniosynostosis, which is similar to results in past studies. 12 Our patients with secondary craniosynostosis had lower mean gestational ages and mean birth weights, which we presume is a natural phenomenon due to overall brain and systemic underdevelopment.…”
Section: Results Of the Tsdo Operative Technique In 285 Children Withsupporting
confidence: 81%
“…Also, the distraction direction vector cannot be adjusted, and thus there is an increased risk of complications, such as bleeding, CSF leakage, subdural space widening, and unwarranted less expansion or overexpansion of the cranium with undesirable cosmetic consequences. 12,13 At present, no studies or information exist on the proper and safe expansion distance in any of the DO surgical techniques, including TSDO, so that determination of this factor is difficult.…”
Section: Discussion Advantages and Limitations Of The Tsdo Operative mentioning
confidence: 99%
“…As reported by Gewalli et al 5 , despite the quick opening of the spring when compared to the established bone distraction procedures 17 , ossification takes place in the gap between the stumps distracted by springs. We agree with the hypothesis that a smaller detachment of the dura mater may be associated to this finding 18 , which is clearly evidenced by Gosain 19 who also observed that the defect created in adult animals was maximized by the maintenance of contact with the pericranium (bone growth from peripheral areas) and dural contact (bone growth from the central area).…”
Section: Discussionmentioning
confidence: 78%
“…In 1998 and 2003, Lauritzen et al 3 described two clinical cases of patients with craniosynostosis using dynamic expansion with implantable internal springs and in 2001, they reported an experimental study showing changes in the growth of rabbit skulls using springs 4 . In 2008, they published the first 100 cases using this device 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The action of springs in infant skulls with malleable bones of membranous nature is not exclusively restricted to bone edges, but extends to adjacent cranial vault. In the first 100 cases, Lauritzen et al (Lauritzen, Davis et al 2008) indicated springs for treating metopic, bicoronal, multisutural synostosis, advancements of the middle third of the face, and others. No serious complications were observed.…”
Section: Expansible Springsmentioning
confidence: 99%